Visualization of cellular surface and intercellular structures of human pluripotent stem cells using electron microscopy techniques - Elmansuri, Rasha (My University, 2022)
Human Induced Pluripotent Stem Cells (hiPSCs) are a classification of stem cells that has the prospect of differentiating into any cell kind in the human body. In his lab in Kyoto, Japan, Shinya Yamanaka 2006 discovered that inducing somatic cells with the factors: Oct4, Sox2, Kif4, and c-myc, reprogram the cells to become iPSCs that are similar in characteristics to Embryonic Stem Cells (ESCs). Research shows extraordinary potential for utilizing hPSCs clinically. However, to date, the ultrastructure and ultrahigh-resolution images of the cellular surface of hPSCs have not been studied. Electron Microscopy (EM) has shown immense potential in visualizing the morphology of cellular surfaces and in-depth structures of biological samples. EM is a microscopy technique that utilizes a shaft of electrons as the primary source of light. This Thesis aimed to visualize the cellular surface of hiPSCs using a Scanning Electron Microscope (SEM) and study the in-depth structures visualized with Transmission Electron Microscope (TEM). In addition, this Thesis aimed to optimize the preparation of hPSCs samples for EM using different protocols. The results of this Thesis highlighted the unique morphology of hiPSCs. TEM imaging results clearly show the limited number of mitochondria ensuring cell stemness. The nucleus, Golgi-apparatus, tight junction, and specific morphological structures were identified in addition to lamellar bodies and glycogen. SEM imaging results at ultrahigh resolution (0.8 nm) clearly show small round-shaped cells, dead cells, filopodia, and filaments.
Keywords: Human Induced Pluripotent Stem Cells, Electron Microscopy, Electron Microscopy Sample Preparation, Transmission Electron Microscopy, Scanning Electron Microscopy